Penerapan Alat Pengasapan Ikan Tipe Kabinet Untuk Meningkatkan Produksi Ikan Asap Di Industri Rumah Tangga Kecamatan Weda Halmahera Tengah - Bambang Tjiroso; Said Hi Abbas (LPPM UMRI, 2020)
Smoked fish is a fish processing product that is very popular with consumers in Indonesia. Smoked fish production in Indonesia, especially in Weda District, Central Halmahera District, still has various problems in the production process because the tools used in daily smoked fish production are still conventional. PKM activity partner is one of the smoked fish home industries located in Weda District, Central Halmahera. Conventional smoking tools are only made of wood and racks made of bamboo and are still open so that the efficiency of smoke for smoking fish is less than optimal. Therefore, through PKM Kubermas, it will be carried out to replace conventional fish smoking equipment owned by partners with cabinet-type smoking equipment to increase production yields. The service implementation process is divided into 7 stages, namely the preparation stage, socialization, making tools, socializing the use of tools, mentoring and evaluation. The results achieved are the dimensions of the smoked fish equipment made with dimensions of length 120 cm, width 80 cm and height 200 cm, while the time required for smoked fish production is more efficient, namely 2 to 3 hours in one production. It uses less fuel at one time because the smoker is closed.